Grazing-induced changes in plant composition affect litter quality and nutrient cycling in Flooding Pampa grasslands - Garibaldi, Lucas Alejandro (2007)
Fil: Garibaldi, Lucas Alejandro. Universidad Nacional del Comahue. Centro Regional Universitario Bariloche. Laboratorio Ecotono; Argentina.